ANALISIS KEMISKINAN DI WILAYAH III CIREBON - Debby Nindya Istiandari (STIE Pelita Nusantara Semarang, 2023)
This is research about the effect of population, mean years of school, and covid-19 on poverty in district/city area III Cirebon including Cirebon City, Cirebon Regency, Indramayu Regency, Majalengka Regency, and Kuningan Regency. The data type in this study was secondary data for the period of 2010-2021 and cross data of five areas, whereas the data analysis technique used was panel data regression analysis. According to the result of analysis, it was found that: (1) the population brings an insignificant positive effect on the poverty, (2) the mean years of school brings a significant negative effect on the poverty, (3) the covid-19 brings a significant negative effect on poverty with the significant rate of 5 percent.